MAELSTROM, a machine learning-based approach for stock assessment - Matteo Stefani; Simone Libralato; Cecilia Pinto; Tommaso Russo (Frontiers in Marine Science, 2026)
Managing the fishing industry is crucial to maintain a balance between the exploitation of marine resources and their natural ability to recover. To achieve such a goal, stock assessment models are built to combine commercial catches and population abundance time series. These approaches can often handle only single-species, losing the information regarding the ecological interactions affecting the dynamics of the species. Moreover, conventional stock assessment models are based on explicit deterministic equations, which can fail to represent the ecological interactions between the species and its environment. In this paper we present Maelstrom, a multispecies predictive model based on neural networks that can interpret fishery-dependent and -independent data to return a forecast of stock abundance considering variations in fishing effort. Although neural networks-based forecasting of ecological and fisheries time series is well established, we present a customizable Shiny tool in which a multi-species, age-structured framing is integrated and devised to be applied in real management frameworks. Namely, we set up five scenarios of increasing complexity in which three commercial species are considered. To assess the model's reliability, we conducted a benchmark test comparing Maelstrom to a routinely used stock assessment tool, the a4a model framework, using RMSE and MAE for validation. The results, besides showing a good degree of accuracy of Maelstrom to classical stock assessment models, endorse the potential of a multi-species approach even when working on shorter time-series. The Shiny application returns statistics, plots, and a report of all the operations conducted during the stock assessment.

Human Stem Cell-Derived Neurospheroids and a Multi-Assay Strategy Provide Brain Cytotoxicity New Insights from ADB-FUBIATA Exposure - Uliana De Simone; Carlo Alessandro Locatelli; Francesca Caloni; Davide Lonati; Luciana Alessandra Russo; Teresa Coccini (Neurotoxicity Research, 2026)

On the move: southern range expansion of Italian parti-coloured bats - Emiliano Mori; Leonardo Ancillotto; Mattia Falaschi; Orly Razgour; Mariella Baratti; Gianna Dondini; Simone Vergari; Andrea Viviano; Ivana Budinski; Marcello Consolo; Penelope Fialas; Renato Pontarini; et al. (Mammalian Biology, 2026)

Performance of the SmartMe&You serious video games for home telemonitoring is related to cognitive status and resting-state electroencephalographic markers in healthy and Parkinson’s disease participants - Claudio Del Percio; Roberta Lizio; Mina De Bartolo; Matteo Carpi; Giuseppe Noce; Susanna Lopez; Antonio Pio Afragola; Federica Fiorentino; Filippo Carducci; Veronica Henao Isaza; Paolo Barone; Arianna Cappiello; et al. (GeroScience, 2026)
Unsupervised serious video games on the SmartMe&You home telemonitoring platform may enable the assessment of cognitive fluctuations in older individuals, with or without cognitive deficits. Here, we tested their validity in cognitively unimpaired older adults (Healthy) and patients with mild cognitive impairment and mild to moderate dementia due to Parkinson’s disease (PDCD). Such validity was assessed using Mini-Mental State Examination (MMSE) scores and resting-state eyes-closed electroencephalography (rsEEG) activity. Clinical, demographic, and rsEEG datasets were collected from 34 healthy and 68 PDCD participants. The SmartMe&You video games included 7 unsupervised cognitive tasks implemented on a commercial tablet. The rsEEG source activities in the individual delta, theta, and alpha frequency bands were estimated using the eLORETA freeware. As novel findings, we showed that game performance: (1) discriminated between healthy participants and PDCD patients, with overall accuracy exceeding 90%; (2) was positively associated with MMSE scores across all participants ( p < 0.00001); and (3) was negatively associated with global rsEEG source activity in the delta and theta frequency bands ( p < 0.00001). These findings suggest that serious videogames of the SmartMe&You home telemonitoring platform were feasible and sensitive to cognitive status across the spectrum from normal aging to Parkinson’s disease-related dementia. This approach provides a scalable, low-cost, and ecologically valid tool for remote cognitive monitoring, with future potential applications in both early detection and longitudinal tracking of cognitive decline.

Vitamin B2 overproduction in Lactiplantibacillus plantarum: new insights in the FMN-dependent regulatory activity of the rib operon riboswitch - Angela Scauro; José Ángel Ruiz-Masó; Annel M. Hernández-Alcántara; Francisca Álvarez-Juárez; Nicola De Simone; Lidia Rodrigo; Rosa Aznar; Pasquale Russo; Giuseppe Spano; Gloria del Solar (Food Bioscience, 2026)

A line with no hook: longline-associated passive eDNA samplers for deep-sea fish monitoring - Martina Spiga; Valentina Crobe; Alice Ferrari; Giulia Maiello; Elia Bueloni; Elisabetta Cilli; Tommaso Russo; Simone Di Crescenzo; Rita Cannas; Giusy Catalano; Corrado Piccinetti; Stefano Mariani; et al. (Marine Environmental Research, 2026)

Postbiotic Potential of Newly Isolated Riboflavin-Overproducing Lactiplantibacillus plantarum Strains - Angela Scauro; Maria Teresa Rocchetti; Mario Soccio; Barbara la Gatta; Maria Teresa Liberatore; Nicola De Simone; Giuseppe Spano; Daniela Fiocco; Pasquale Russo (Probiotics and Antimicrobial Proteins, 2026)
Lactic acid bacteria (LAB) are food-grade microorganisms able to produce and release bioactive compounds of interest to human health. Some LAB strains can synthesize vitamin B2, i.e., riboflavin, a micronutrient essential for cellular metabolism. In this work, six Lactiplantibacillus plantarum isolated from fruits of the Mediterranean area were exposed to the selective pressure of roseoflavin in order to select spontaneous riboflavin-overproducing phenotypes. The best strains, as determined by the level of riboflavin produced, were characterized for some basic probiotic features, including antibacterial activity, production of organic acids, antibiotic resistance, and survival under digestive stresses using an in vitro gut model. The strain L. plantarum Lp 187_B2 , which produced the highest riboflavin level (6 mg/L), exhibited good resistance to gastro-intestinal stress and a relevant capacity to antagonize undesired bacteria, was selected for additional investigations to assess its capacity to protect intestinal homeostasis. When used as a postbiotic, Lp 187_B2 significantly increased trans-epithelial electrical resistance (TEER) in Caco-2 cell monolayers, an in vitro model of the intestinal barrier. Moreover, in a Caco-2/THP-1 co-culture system, mimicking the inflamed bowel, Lp 187_B2 postbiotics significantly inhibited the release of TNF-α by macrophages, thus pointing to gut-barrier strengthening and potential anti-inflammatory properties. Though a validation in vivo is required, our preliminary results indicate that L. plantarum Lp 187_B2 could be successfully applied as both probiotic and postbiotic formulations for improving human health.

Heyndrickxia coagulans LMG S-24828 Is a Safe Probiotic Strain Capable of Germinating in the Human Gut - Robin Duncan; Giacomo Mantegazza; Giorgio Gargari; Elena Pierallini; Rosario Russo; Simone Guglielmetti (Probiotics and Antimicrobial Proteins, 2025)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Highly sensitive detection of different aggregation stages of Aβ1-42 -amyloid peptide in urine-like samples by auto-fluorescence - Concetta Di Natale; Sara La Manna; Stefania Carbone; Sara Coppola; Veronica Vespini; Volodymyr Tkachenko; Daniele Tammaro; Simone Russo; Giuseppe Vitiello; Giuseppina Luciani; Daniela Marasco; Pier Luca Maffettone; et al. (Analytica Chimica Acta, 2025)

Contamination of alpine pastures by Mycobacterium avium subsp. paratuberculosis: Evaluation of cattle and red deer contribution through environmental fecal samples - Chiara Garbarino; Matteo Nava; Anita Filippi; Alessandro Forti; Simone Russo; Filippo Barsi; Alessandro Bianchi; Joel Filipe; Norma Arrigoni; Luca Pedrotti; Luca Corlatti; Matteo Ricchi; et al. (Veterinary Microbiology, 2025)

Sunlight driven photo-treatment of polyhydroxybutyrate microplastics mediated by carbon nanodots-doped ZnO mesocrystals: Induced surface changes boost degradation in soil and biofilm formation - Simone Russo; Marica Muscetta; Immacolata Liotta; Moreno Rizzo; Daniele Marra; Gennaro Gentile; Beate Förster; Sergio Caserta; Raffaele Marotta; Mariacristina Cocca; Giuseppe Vitiello (Journal of Hazardous Materials, 2025)

The hidden constrains in soil ecology and plant physiology: microplastic effects on nutrient and metal transport in soil-plant continuum - Simone Landi; Giorgia Santini; Noemi Russo; Lucia Santorufo; Karen Power; Luigi Rosati; Antonietta Siciliano; Alessandra Marano; Carmen Arena; Sergio Esposito; Giulia Maisto (Plant and Soil, 2025)

Simulated gastrointestinal digestion of two convenience meals using fungal enzyme formulations - Robin Duncan; Giacomo Mantegazza; Claudio Gardana; Fabio Angelini; Rosario Russo; Simone Guglielmetti (Food Bioscience, 2025)

Green hydrogen production: energy and economic modelling of self-sufficient solar-powered electrolyser based on seawater desalination - Annamaria Buonomano; Paolo de Simone; Giovanni Francesco Giuzio; Robert Maka; Adolfo Palombo; Giuseppe Russo (Journal of Cleaner Production, 2025)

Assessing the activity and stability of Cu2O/SnO2-based gas diffusion electrodes for the CO2 conversion in different electrolytes: Bicarbonate vs. Ionic Liquid/Acetonitrile - Federica Zammillo; Hilmar Guzmán; Daniela Polino; Roger Miró; Alberto Lopera; Emmanuele Parisi; Alessia Fortunati; Maddalena Zoli; Elena Simone; Nunzio Russo; Mariajose López-Tendero; Miriam Díaz de los Bernardos; et al. (Chemical Engineering Journal, 2025)

Taxonomy for conservation: multi-taxa survey evidences a biodiversity hotspot in the Central Apennines (Salto-Cicolano District) - Pierangelo Crucitti; Danilo Russo; Giovanni Amori; Marcello Vitale; Corrado Battisti; Roberto Antonelli; Davide Brocchieri; Marco Giardini; Luigi Lenzini; Paolo Mazzei; Nicolò Pellecchia; Luca Tringali; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

The effect of marine litter on fishery economic performance - Alice Sbrana; Simone Galli; Tommaso Russo (Fisheries Research, 2025)

Corrigendum to “Food web analysis shows an exacerbated dependence of zooplankton on detritus in oligotrophic systems due to ocean warming” [Prog. Oceanogr. 231 (2025) 103389] - Luca Russo; Matteo Loschi; Daniele Bellardini; Roberta Congestri; Michael W. Lomas; Simone Libralato; Domenico D’Alelio (Progress in Oceanography, 2025)

Food web analysis shows an exacerbated dependence of zooplankton on detritus in oligotrophic systems due to ocean warming - Luca Russo; Matteo Loschi; Daniele Bellardini; Roberta Congestri; Michael W. Lomas; Simone Libralato; Domenico D’Alelio (Progress in Oceanography, 2025)

Modeling the spatial distribution and abundance of deep‐water red shrimps in the Mediterranean Sea: a machine learning approach - Elena Catucci; Diego Panzeri; Simone Libralato; Gianpiero Cossarini; Germana Garofalo; Irida Maina; Stefanos Kavadas; Federico Quattrocchi; Giulia Cipriano; Roberto Carlucci; Sergio Vitale; Chryssi Mytilineou; et al. (Fisheries Research, 2025)

Probiotic Lactiplantibacillus plantarum strains showing anti-Botrytis activity: A food-grade approach to improve the overall quality of strawberry in post-harvest - Nicola De Simone; Angela Scauro; Danial Fatchurrahman; Maria Luisa Amodio; Vittorio Capozzi; Giancarlo Colelli; Giuseppe Spano; Mariagiovanna Fragasso; Pasquale Russo (Postharvest Biology and Technology, 2024)

Immunomodulatory Activity on Human Macrophages by Cell-Free Supernatants to Explore the Probiotic and Postbiotic Potential of Lactiplantibacillus plantarum Strains of Plant Origin - Maria Teresa Rocchetti; Pasquale Russo; Nicola De Simone; Vittorio Capozzi; Giuseppe Spano; Daniela Fiocco (Probiotics and Antimicrobial Proteins, 2024)
Upon dietary administration, probiotic microorganisms can reach as live cells the human gut, where they interact with the microbiota and host cells, thereby exerting a beneficial impact on host functions, mainly through immune-modulatory activities. Recently, attention has been drawn by postbiotics, i.e. non-viable probiotic microbes, including their metabolic products, which possess biological activities that benefit the host. Lactiplantibacillus plantarum is a bacterial species that comprises recognised probiotic strains. In this study, we investigated in vitro the probiotic (and postbiotic) potential of seven L. plantarum strains, including five newly isolated from plant-related niches. The strains were shown to possess some basic probiotic attributes, including tolerance to the gastrointestinal environment, adhesion to the intestinal epithelium and safety. Besides, their cell-free culture supernatants modulated cytokine patterns in human macrophages in vitro, promoting TNF-α gene transcription and secretion, while attenuating the transcriptional activation and secretion of both TNF-α and IL-8 in response to a pro-inflammatory signal, and enhancing the production of IL-10. Some strains induced a high IL-10/IL-12 ratio that may correlate to an anti-inflammatory capacity in vivo. Overall, the investigated strains are good probiotic candidates, whose postbiotic fraction exhibits immunomodulatory properties that need further in vivo studies. The main novelty of this work consists in the polyphasic characterisation of candidate beneficial L. plantarum strains obtained from relatively atypical plant-associated niches, by an approach that explores both probiotic and postbiotic potentials, in particular studying the effect of microbial culture-conditioned media on cytokine pattern, analysed at both transcriptional and secretion level in human macrophages.

Environmental DNA metabarcoding reveals the effects of seafloor litter and trawling on marine biodiversity - Alice Sbrana; Giulia Maiello; Maria Flavia Gravina; Davide Cicala; Simone Galli; Matteo Stefani; Tommaso Russo (Marine Environmental Research, 2024)

Antifungal activity of Lactiplantibacillus plantarum isolated from fruit and vegetables and detection of novel antifungal VOCs from fungal-LAB co-cultures - Nicola De Simone; Lucía López; Carmen S. Ciudad; Angela Scauro; Pasquale Russo; Jorge Rodríguez; Giuseppe Spano; Beatriz Martínez (Food Bioscience, 2024)

Identifying priority areas for spatial management of mixed fisheries using ensemble of multi‐species distribution models - Diego Panzeri; Tommaso Russo; Enrico Arneri; Roberto Carlucci; Gianpiero Cossarini; Igor Isajlović; Svjetlana Krstulović Šifner; Chiara Manfredi; Francesco Masnadi; Marco Reale; Giuseppe Scarcella; Cosimo Solidoro; et al. (Fish and Fisheries, 2024)
Spatial fisheries management is widely used to reduce overfishing, rebuild stocks, and protect biodiversity. However, the effectiveness and optimization of spatial measures depend on accurately identifying ecologically meaningful areas, which can be difficult in mixed fisheries. To apply a method generally to a range of target species, we developed an ensemble of species distribution models (e‐SDM) that combines general additive models, generalized linear mixed models, random forest, and gradient‐boosting machine methods in a training and testing protocol. The e‐SDM was used to integrate density indices from two scientific bottom trawl surveys with the geopositional data, relevant oceanographic variables from the three‐dimensional physical‐biogeochemical operational model, and fishing effort from the vessel monitoring system. The determined best distributions for juveniles and adults are used to determine hot spots of aggregation based on single or multiple target species. We applied e‐SDM to juvenile and adult stages of 10 marine demersal species representing 60% of the total demersal landings in the central areas of the Mediterranean Sea. Using the e‐SDM results, hot spots of aggregation and grounds potentially more selective were identified for each species and for the target species group of otter trawl and beam trawl fisheries. The results confirm the ecological appropriateness of existing fishery restriction areas and support the identification of locations for new spatial management measures.

Corrigendum: Spatial analysis of demersal food webs through integration of eDNA metabarcoding with fishing activities - Davide Cicala; Giulia Maiello; Fabio Fiorentino; Germana Garofalo; Daniela Massi; Alice Sbrana; Stefano Mariani; Simone D’Alessandro; Matteo Stefani; Lucie Perrodin; Tommaso Russo (Frontiers in Marine Science, 2024)

What, where, and when: Spatial-temporal distribution of macro-litter on the seafloor of the western and central Mediterranean sea - Alessandro Cau; Alice Sbrana; Simone Franceschini; Fabio Fiorentino; Maria Cristina Follesa; Francois Galgani; Germana Garofalo; Olivia Gerigny; Adriana Profeta; Paola Rinelli; Mario Sbrana; Tommaso Russo (Environmental Pollution, 2024)

Spatial analysis of demersal food webs through integration of eDNA metabarcoding with fishing activities - Davide Cicala; Giulia Maiello; Fabio Fiorentino; Germana Garofalo; Daniela Massi; Alice Sbrana; Stefano Mariani; Simone D’Alessandro; Matteo Stefani; Lucie Perrodin; Tommaso Russo (Frontiers in Marine Science, 2024)
The evaluation of the status of marine communities, and especially the monitoring of those heavily exploited by fisheries, is a key, challenging task in marine sciences. Fishing activities are a major source of disruption to marine food webs, both directly, by selectively removing components at specific trophic levels (TL), and indirectly, by altering habitats and production cycles. Food web analysis can be very useful in the context of an Ecosystem Approach to Fisheries, but food web reconstructions demand large and expensive data sets, which are typically available only for a small fraction of marine ecosystems. Recently, new technologies have been developed to easily, quickly and cost-effectively collect environmental DNA (eDNA) during fishing activities. By generating large, multi-marker metabarcoding data from eDNA samples obtained from commercial trawlers, it is possible to produce exhaustive taxonomic inventories for the exploited ecosystems, which are suitable for food-web reconstructions. Here, we integrate and re-analyse the data of a recent study in which the α diversity was investigated using the eDNA opportunistically collected during fishing operations. Indeed, we collect highly resolved information on species feeding relationships to reconstruct the food webs at different sites in the Strait of Sicily (Mediterranean Sea) from eDNA and catch data. After observing that the trophic networks obtained from eDNA metabarcoding data are more consistent with the available knowledge, a set of food web indicators (species richness, number of links, direct connectance and generality) is computed and analysed to unravel differences in food webs structure through different areas (spatial variations). Species richness, number of links and generality (positively) and direct connectance (negatively) are correlated with increasing distance from the coast and fishing effort intensity. The combined effects of environmental gradients and fishing effort on food web structure at different study sites are then examined and modelled. Taken together, these findings indicate the suitability of eDNA metabarcoding to assist and food web analysis, obtain several food web-related ecological indicators, and tease out the effect of fishing intensity from the environmental gradients of marine ecosystems.

Humic substance/metal-oxide multifunctional nanoparticles as advanced antibacterial-antimycotic agents and photocatalysts for the degradation of PLA microplastics under UVA/solar radiation - Simone Russo; Marica Muscetta; Paola Amato; Virginia Venezia; Mariavittoria Verrillo; Romina Rega; Stefano Lettieri; Mariacristina Cocca; Raffaele Marotta; Giuseppe Vitiello (Chemosphere, 2024)

Meso- and microplastic composition, distribution patterns and drivers: A snapshot of plastic pollution on Brazilian beaches - Tamyris Pegado; Ryan Andrades; Eurico Noleto-Filho; Simone Franceschini; Marcelo Soares; David Chelazzi; Tommaso Russo; Tania Martellini; Angelica Barone; Alessandra Cincinelli; Tommaso Giarrizzo (Science of The Total Environment, 2024)

Antimicrobial Properties, Functional Characterisation and Application of Fructobacillus fructosus and Lactiplantibacillus plantarum Isolated from Artisanal Honey - Nicola De Simone; Maria Teresa Rocchetti; Barbara la Gatta; Giuseppe Spano; Djamel Drider; Vittorio Capozzi; Pasquale Russo; Daniela Fiocco (Probiotics and Antimicrobial Proteins, 2023)
Honey is a valuable reservoir of lactic acid bacteria (LAB) and, particularly, of fructophilic LAB (FLAB), a relatively novel subgroup of LAB whose functional potential for human and food application has yet to be explored. In this study, FLAB and LAB strains have been isolated from honeys of different floral origins and selected for their broad antimicrobial activity against typical foodborne pathogenic bacteria and spoilage filamentous fungi. The best candidates, two strains belonging to the species Lactiplantibacillus plantarum and Fructobacillus fructosus , were submitted to partial characterisation of their cell free supernatants (CFS) in order to identify the secreted metabolites with antimicrobial activity. Besides, these strains were examined to assess some major functional features, including in vitro tolerance to the oro-gastrointestinal conditions, potential cytotoxicity against HT-29 cells, adhesion to human enterocyte-like cells and capability to stimulate macrophages. Moreover, when the tested strains were applied on table grapes artificially contaminated with pathogenic bacteria or filamentous fungi, they showed a good ability to antagonise the growth of undesired microbes, as well as to survive on the fruit surface at a concentration that is recommended to develop a probiotic effect. In conclusion, both LAB and FLAB honey-isolated strains characterised in this work exhibit functional properties that validate their potential use as biocontrol agents and for the design of novel functional foods. We reported antimicrobial activity, cytotoxic evaluation, probiotic properties and direct food application of a F. fructosus strain, improving the knowledge of this species, in particular, and on FLAB, more generally.

Coupling Lagrangian simulation models and remote sensing to explore the environmental effect on larval growth rate: The Mediterranean case study of round sardinella (Sardinella aurita) early life stages - Marco Torri; Stefania Russo; Federico Falcini; Biagio De Luca; Simone Colella; Gianluca Volpe; Raffaele Corrado; Francesco Placenti; Luigi Giaramita; Marianna Musco; Tiziana Masullo; Carmelo Bennici; et al. (Frontiers in Marine Science, 2023)
The relationship between environmental conditions and early life-history traits of Sardinella aurita are investigated using material collected in two sites of the Central Mediterranean Sea. Individual mean daily growth during the planktonic phase has been determined by using otolith microstructure analysis, while Lagrangian simulation models allowed to estimate the daily position in space and time of each specimen from the hatching to the catch. Generalized Additive Mixed Models (GAMMs) have been implemented to explore the impact of environmental conditions at time t , t -1 day and t -2 days on the mean daily growth rate occurring at time t . Spatial analysis evidenced a wide dispersion of eggs and larvae in the coastal area of both sampling sites in correspondence to relatively warmer and chlorophyll-a enriched waters. Lagrangian simulations detected a complementary larval dispersal pathway able to transport larvae to a known retention area. Temperature at time t was the most important driver affecting the mean daily larval growth, followed by the food availability. On the other hand, models performed on lagged environmental covariates ( t -1 and t -2) did not show any significant effect on the growth rate at time t . In addition to the sub-linear positive correlation between temperature and mean daily larval growth, model highlighted a decrease in the otolith core width at higher temperature that can be linked to an earlier stage of ontogeny at hatching. This study provided a useful methodological approach that takes advantage of available remote sensing data to perform ecological studies in support to fisheries management.

New Technologies to Diagnose and Treat a Multidrug-Resistant Candida auris: A Patent Review - Luana Rossato; Simone Simionatto; Mairim Russo Serafini; Izabel Almeida Alves (Mycopathologia, 2022)

Editorial: Fishing in the time of COVID-19: Effects on fishing activities, resources, and marine ecosystems - Tommaso Russo; Sebastian Villasante; Simone Libralato (Frontiers in Marine Science, 2022)

Interactive effects of fishing effort reduction and climate change in a central Mediterranean fishing area: Insights from bio-economic indices derived from a dynamic food-web model - Davide Agnetta; Fabio Badalamenti; Francesco Colloca; Gianpiero Cossarini; Fabio Fiorentino; Germana Garofalo; Bernardo Patti; Carlo Pipitone; Tommaso Russo; Cosimo Solidoro; Simone Libralato (Frontiers in Marine Science, 2022)
Disentangling the effects of mixed fisheries and climate change across entire food-webs requires a description of ecosystems using tools that can quantify interactive effects as well as bio-economic aspects. A calibrated dynamic model for the Sicily Channel food web, made up of 72 functional groups and including 13 fleet segments, was developed. A temporal simulation until 2050 was conducted to evaluate the bio-economic interactive effects of the reduction of bottom trawling fishing effort by exploring different scenarios that combine fishery and climate change. Our results indicate that direct and indirect effects produce a net increase in biomass of many functional groups with immediate decline of trawlers’ catches and economic incomes, followed by a long term increase mainly due to biomass rebuilding of commercial species which lasts 5-10 years after fishing reduction. Synergistic and antagonistic effects caused by changes in the fishing effort and in climate characterize a specific functional group’s response in biomass which, in turn, modulate also the catch and income of the other fleets, and especially of those sharing target resources. However, trawler’s intra-fleet competition is higher than the others fleet effects. In the medium term, the effects of fishing effort reduction are higher than those of climate change and seem to make exploitation of marine resources more sustainable over time and fishery processes more efficient by improving ecosystem health.

Ask the shark: blackmouth catshark (Galeus melastomus) as a sentinel of plastic waste on the seabed - Alice Sbrana; Alessandro Cau; Davide Cicala; Simone Franceschini; Tommaso Giarrizzo; Maria Flavia Gravina; Alessandro Ligas; Giulia Maiello; Marco Matiddi; Antonio Parisi; Paolo Sartor; Mario Sbrana; et al. (Marine Biology, 2022)
The presence of plastic waste in the marine environment has driven the scientific community to make significant efforts to study and mitigate its possible effects. One of the critical aspects is to determine if and how an increase in ingestion events may occur as a result of the accumulation of plastic waste on the seabed. In this study, G. melastomus is examined for its ability to indirectly provide information on the amount of macroplastics accumulating on the seafloor. Plastic ingestion is explored by describing the feeding habits of the species, which have the potential to provide very useful information regarding biological or ecological issues. The diet of G. melastomus mainly consisted of cephalopods, bathypelagic fishes, and decapod crustaceans, increasing in diversity during growth. The generalist-opportunistic feeding behaviour of this species leads to the incidental ingestion of plastic particles ( N = 47, with a mean (± SD) of 1.47 ± 0.28 per specimen) which can be indirectly associated to the presence of macroplastics on the seafloor. Indeed, our results indicate a significant relationship between the amount of macroplastics present on the seabed and the frequency of ingestion of plastic particles by blackmouth catshark. We propose G. melastomus as an excellent candidate for developing a valid monitoring strategy for the presence of plastics on the seabed, as requested by the EU Marine Strategy Framework Directive.

Defend as You Can, React Quickly: The Effects of the COVID-19 Shock on a Large Fishery of the Mediterranean Sea - Tommaso Russo; Elena Catucci; Simone Franceschini; Lucio Labanchi; Simone Libralato; Evelina Carmen Sabatella; Rosaria Felicita Sabatella; Antonio Parisi; Fabio Fiorentino (Frontiers in Marine Science, 2022)
This paper presents an analysis of the effect of SARS-CoV-2 coronavirus pandemic and related restrictive measures on the activity of the Italian fleet of trawlers, which represents one of the most important fisheries in the Mediterranean Sea. We integrated multiple sources of information including: (1) Fleet activity data from Vessel Monitoring System, the most important satellite-based tracking device; (2) vessel-specific landing data disaggregated by species; (3) market and economic drivers affecting the effort variation during the lockdown and in the related fishing strategies; (4) monthly landings of demersal species in the main Italian harbors. These data sources are combined to: (1) Assess the absolute and relative changes of trawling effort in the geographical sub-areas surrounding the Italian coasts; (2) integrate and compare these changes with the market and economic drivers in order to explain the observed changes in fishing effort and strategy; (3) analyze the changes of the fishing effort on the Landing-per-unit-effort (LPUE) in order to further understand the strategy adopted by fishers during this crisis and to infer the potential consequence for the different stocks. The results provide an overview of the effects of the “COVID-19 shock,” in terms of fishing activity and socio-economic drivers, demonstrating that the consequences of the pandemic have been very varied. Although the COVID-19 shock has caused a marked overall reduction in activity in the first semester of 2020, in some cases the strategies adopted by fishermen and the commercial network linked to their activity have significantly reduced the impact of the emergency and taken back catch and effort to levels similar to those of previous years. These results could provide insights for management measures based on temporal stops of fishing activities. In particular, if no limits to the fishing effort after the restart of fishing activities are adopted, the benefits of fishing pressure reduction on fishery resources could be nullified. On the other hands, when fishing activities restart, and in the absence of catch control, effort tends to increase on coastal bottoms characterized by greater abundance of resources and longer effective fishing time.

Investigation of levels of perfluoroalkyl substances in freshwater fishes collected in a contaminated area of Veneto Region, Italy - Federica Gallocchio; Marzia Mancin; Simone Belluco; Alessandra Moressa; Roberto Angeletti; Monica Lorenzetto; Giuseppe Arcangeli; Nicola Ferrè; Antonia Ricci; Francesca Russo (Environmental Science and Pollution Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genetic testing and surveillance in infantile myofibromatosis: a report from the SIOPE Host Genome Working Group - Simone Hettmer; Guillaume Dachy; Guido Seitz; Abbas Agaimy; Catriona Duncan; Marjolijn Jongmans; Steffen Hirsch; Iris Kventsel; Uwe Kordes; Ronald R. de Krijger; Markus Metzler; Orli Michaeli; et al. (Familial Cancer, 2021)
Infantile myofibromatosis (IM), which is typically diagnosed in young children, comprises a wide clinical spectrum ranging from inconspicuous solitary soft tissue nodules to multiple disseminated tumors resulting in life-threatening complications. Familial IM follows an autosomal dominant mode of inheritance and is linked to PDGFRB germline variants. Somatic PDGFRB variants were also detected in solitary and multifocal IM lesions. PDGFRB variants associated with IM constitutively activate PDGFRB kinase activity in the absence of its ligand. Germline variants have lower activating capabilities than somatic variants and, thus, require a second cis-acting hit for full receptor activation. Typically, these mutant receptors remain sensitive to tyrosine kinase inhibitors such as imatinib. The SIOPE Host Genome Working Group, consisting of pediatric oncologists, clinical geneticists and scientists, met in January 2020 to discuss recommendations for genetic testing and surveillance for patients who are diagnosed with IM or have a family history of IM/ PDGFRB germline variants. This report provides a brief review of the clinical manifestations and genetics of IM and summarizes our interdisciplinary recommendations.

Eating Near the Dump: Identification of Nearby Plastic Hotspot as a Proxy for Potential Microplastic Contamination in the Norwegian Lobster (Nephrops norvegicus) - Simone Franceschini; Alessandro Cau; Lorenzo D’Andrea; Maria Cristina Follesa; Tommaso Russo (Frontiers in Marine Science, 2021)
Plastic waste dumped in the marine environment has severe ecological, social and economic impacts. In recent years, a series of scientific studies documented the contamination by macroplastic and its impact on marine organisms through the accidental ingestion of microplastics, which also originate from the degradation of macroplastic. However, the relationship between the spatial distribution of marine litter and the ingestion of plastics by organisms have never been related. In this work, we aimed to investigate, through a modeling approach, the relations between potential sources of microplastic particles (i.e., seafloor macroplastic accumulation hotspots detected by means of trawl surveys), and the ingestion by the benthic crustacean Norwegian lobster ( Nephrops norvegicus ). According to the literature, N. norvegicus is characterized by a sedentary behavior and therefore it has been highlighted as a proficient sentinel species for local microplastic contamination. Despite no significant relation has been found between microplastic ingestion and the local presence of seafloor macroplastic, it seems that proximity to hotspots of macroplastic accumulation is significantly related to microplastics ingestion. These results highlight important considerations on the fate of plastic in the marine environments with significant impacts on biota and the quality of the product caught at sea.

The MINOUWApp: a web-based tool in support of by-catch and discards management - Lorenzo D’Andrea; Aida Campos; Karim Erzini; Paulo Fonseca; Simone Franceschini; Stefanos Kavadas; Irida Maina; Francesc Maynou; Tommaso Russo (Environmental Monitoring and Assessment, 2020)
Current fishing practices often do not allow adequate selection of species or sizes of fish, resulting in unwanted catches, subsequently discarded, with the consequent negative effects on both marine communities and fisheries profitability. The cross-analysis of density patches of potential unwanted catches and distribution of fishing effort can support the identification of spatial-temporal hot-spots in which the fishing pressure should be reduced to limit the amount of discards. The MinouwApp represents a technological and methodological framework to bring different, and structurally complex, sources of georeferenced data together into a simple visual interface aiming to interactively explore temporal ranges and areas of interest. The objective is to improve the understanding of fisheries dynamics, including discards, thus contributing to the implementation of discard management plans in a context of participative, ecosystem-based fisheries management strategies.

Predicting Fishing Footprint of Trawlers From Environmental and Fleet Data: An Application of Artificial Neural Networks - Tommaso Russo; Simone Franceschini; Lorenzo D’Andrea; Michele Scardi; Antonio Parisi; Stefano Cataudella (Frontiers in Marine Science, 2019)

Simulating the Effects of Alternative Management Measures of Trawl Fisheries in the Central Mediterranean Sea: Application of a Multi-Species Bio-economic Modeling Approach - Tommaso Russo; Lorenzo D'Andrea; Simone Franceschini; Paolo Accadia; Andrea Cucco; Germana Garofalo; Michele Gristina; Antonio Parisi; Giovanni Quattrocchi; Rosaria Felicita Sabatella; Matteo Sinerchia; Donata M. Canu; et al. (Frontiers in Marine Science, 2019)

Trends in Effort and Yield of Trawl Fisheries: A Case Study From the Mediterranean Sea - Tommaso Russo; Paolo Carpentieri; Lorenzo D’Andrea; Paola De Angelis; Fabio Fiorentino; Simone Franceschini; Germana Garofalo; Lucio Labanchi; Antonio Parisi; Michele Scardi; Stefano Cataudella (Frontiers in Marine Science, 2019)

Multi-hazard assessment in Europe under climate change - Giovanni Forzieri; Luc Feyen; Simone Russo; Michalis Vousdoukas; Lorenzo Alfieri; Stephen Outten; Mirco Migliavacca; Alessandra Bianchi; Rodrigo Rojas; Alba Cid (Climatic Change, 2016)

Evolution of the Sele River coastal plain (southern Italy) during the Late Quaternary by inland and offshore stratigraphical analyses - Pietro P. C. Aucelli; Vincenzo Amato; Francesca Budillon; Maria Rosaria Senatore; Sabrina Amodio; Carmine D’Amico; Simone Da Prato; Luciana Ferraro; Gerardo Pappone; Elda Russo Ermolli (Rendiconti Lincei. Scienze Fisiche e Naturali, 2012)

Holocene environmental evolution of the costal sector in front of the Poseidonia-Paestum archaeological area (Sele plain, southern Italy) - Vincenzo Amato; Pietro Patrizio Ciro Aucelli; Bruno D’Argenio; Simone Da Prato; Luciana Ferraro; Gerardo Pappone; Paola Petrosino; Carmen Maria Rosskopf; Elda Russo Ermolli (Rendiconti Lincei. Scienze Fisiche e Naturali, 2012)

Reworking the idea of chestnut ( Castanea sativa Mill.) cultivation in Roman times: New data from ancient Campania - G. Di Pasquale; E. Allevato; E. Russo Ermolli; S. Coubray; C. Lubritto; F. Marzaioli; M. Yoneda; K. Takeuchi; Y. Kano; S. Matsuyama; G. F. De Simone (Plant Biosystems, 2010)